2018
DOI: 10.1016/j.mod.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function Shh mutants activate Smo cell-autonomously independent of Ptch1/2 function

Abstract: Sonic Hedgehog (Shh) signaling is characterized by non-cell autonomy; cells expressing Shh do not respond to the ligand. Here, we identify several Shh mutations that can activate the Hedgehog (Hh) pathway cell-autonomously. Cell-autonomous pathway activation requires the extracellular cysteine rich domain of Smoothened, but is otherwise independent of the Shh receptors Patched1 and -2. Many of the Shh mutants that gain activity fail to undergo auto processing resulting in the perdurance of the Shh pro-peptide,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…While Hh canonical Hh signaling is typically induced in a "mesemchymal type" cell by a fully process 19 kDa N-Shh form produced by an "epithelial like" cells, Hh signaling in ECs occur through a noncanonical autocrine signaling. Consistent with the present finding such signaling was shown to be induced by full length-unprocessed Hh ligands 31 . However the molecular mechanisms by which 43 kDa FL-Dhh promotes endothelial barrier function remains to be characterized.…”
Section: Discussionsupporting
confidence: 93%
“…While Hh canonical Hh signaling is typically induced in a "mesemchymal type" cell by a fully process 19 kDa N-Shh form produced by an "epithelial like" cells, Hh signaling in ECs occur through a noncanonical autocrine signaling. Consistent with the present finding such signaling was shown to be induced by full length-unprocessed Hh ligands 31 . However the molecular mechanisms by which 43 kDa FL-Dhh promotes endothelial barrier function remains to be characterized.…”
Section: Discussionsupporting
confidence: 93%
“…First we tested whether Gas1 or Cdon modulate Dhh interaction with Ptch1 and Smo. Notably, Smo has been recently shown to be a receptor for Hh ligands especially in the case of cell autonomous signaling (Casillas et Roelink 2018). Interestingly, we found that Gas1 prevents Dhh interaction with Ptch1 but promotes Dhh interaction with Smo.…”
Section: Gas1 Promotes Dhh Interaction With Smo While Cdon Prevents Dmentioning
confidence: 58%
“…Mutating the residues directly involved in the coordination of zinc are obvious candidates to assess a role for the putative peptidase activity. However, Shh mutants in the zinc coordination domain could barely be detected the N-terminal processed form (ShhNp) on Western Blots, despite normal detection of the Shh pro-protein (Casillas and Roelink, 2018). We and others (Traiffort et al, 2004) initially incorrectly interpreted this as a failure of auto-processing, but the same low levels were observed analyzing these mutants in Shh-C199*, a Shh mutant truncated at the auto-processing site (ShhN) (Roelink et al, 1995).…”
Section: Mutations In the Zinc Coordination Domain Reduce The Stabilimentioning
confidence: 93%
“…The Dynamin inhibitor Dynasore (that inhibits endocytosis) (Macia et al, 2006) causes strong accumulation of Shh-C199*, but not of Shh-C199*/H183A, further indicating that the destabilization of Shh-C199*/H183A occurs before it reaches the plasma membrane ( Figure 2E). We found that other zinc coordination mutations as well as several holoprosencephaly-associated point mutations in Shh cause its destabilization, indicating a role for increased ShhN degradation in this birth defect (Casillas and Roelink, 2018). In general, we will not use these mutants with a reduced half-life.…”
Section: Mutations In the Zinc Coordination Domain Reduce The Stabilimentioning
confidence: 99%
See 1 more Smart Citation